2002
DOI: 10.1177/107769580205700403
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Technological Change on Journalism Education: A Survey of Faculty and Administrators

Abstract: Wasn't the information age supposed to make professional work more productive and less tedious, therefore less stressful? Sometimes it just doesn't seem that way.This study was inspired by a national survey of postsecondary faculty produced by the Higher Education Research Institute at UCLA.' The UCLA study included a number of personal and attitudinal measures about the faculty life, but professors also provided information about some aspects of their use of technology, including how much stress they perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…Some also strongly suggest curricula that teach journalism as community focused, as a course of study that focuses on basic reporting skills while incorporating technology (Mensing, 2010). Finding the right balance between the basics and new technologies remains elusive, and instructors have always been slow to adapt to new technologies and incorporate them into curriculum (e.g., Beard, 1991;Singer et al, 1996;Voakes, Beam, & Ogan, 2002). One concern facing journalism educators when designing a curriculum revolves around how much it should focus on emerging technologies: Should they become the center of all curricula at the expense of more traditional skills or does there need to be a balance (C. W. Anderson, 2014)?…”
Section: Journalism Education and Technologymentioning
confidence: 99%
“…Some also strongly suggest curricula that teach journalism as community focused, as a course of study that focuses on basic reporting skills while incorporating technology (Mensing, 2010). Finding the right balance between the basics and new technologies remains elusive, and instructors have always been slow to adapt to new technologies and incorporate them into curriculum (e.g., Beard, 1991;Singer et al, 1996;Voakes, Beam, & Ogan, 2002). One concern facing journalism educators when designing a curriculum revolves around how much it should focus on emerging technologies: Should they become the center of all curricula at the expense of more traditional skills or does there need to be a balance (C. W. Anderson, 2014)?…”
Section: Journalism Education and Technologymentioning
confidence: 99%
“…Technical Support (lack of). Not only do we consider stressful demands caused or mediated by ICT, but also the lack of resources to deal with such demands (e.g., inadequate technical support being in itself a source of distress, Ogan and Chung, 2002;Voakes et al, 2003;Al-Fudail and Mellar, 2008). 14.…”
mentioning
confidence: 99%
“…Furthermore, this study also showed how few techniques and resources are being used in the classroom to teach the subject (i.e., data analysis, mathematical techniques, web scraping) despite these investigative journalism skills being common in today's newsrooms. This study contributes to existing scholarship on the gap between the academy and the profession (Clark, 2013;Cleary, 2003;Dennis et al, 2002;Du & Thornburg, 2011;Glasser, 2006;Hanusch et al, 2015;Mensing & Ryfe, 2013;Nolan, 2008;Reese, 1999;Voakes et al, 2003).…”
Section: Discussionmentioning
confidence: 81%